Meningkatkan Motivasi Belajar Siswa dengan Menerapkan Ice Breaking dengan Teknik Stop - Arsa, Nyoman L Dibya; Astuti, Putu Sri; Munir, Misbachol (Sahabat Akademia Group, 2024)
This research aims to describe the application of the ice-breaking stop technique aimed at increasing student learning motivation. Ice-breaking is a strategy that can be used to get students excited and concentrated in the learning process. Stop technique, stopping all activities temporarily for a moment to catch your breath and calm students' minds before receiving thematic learning. The method used is descriptive-qualitative. This research was carried out at SD Negeri 3 Banyupoh, Gerokgak District, Buleleng Regency. The subjects of this research were grade 3 students. Based on the results of observations and interviews, the average student felt happy learning with ice-breaking activities and stop techniques. Students felt calmer and more focused after performing the stop technique. Students said they were more enthusiastic and motivated to participate in learning because they were no longer sleepy. Feelings of tiredness and sleepiness disappear when doing ice-breaking activities. There are several obstacles faced in using the stop technique, including facilities and networks, so it is anticipated to prepare the media before learning begins.